STUDY OF THE POTENTIAL AND STRATEGY OF RAW WATER RESOURCE MANAGEMENT TO MEET THE NEED FOR SUSTAINABLE CLEAN WATER IN TANJUNGBALAI CITY - Rahmat Fauzi; Cut Nuraini; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2025)
Fulfillment of clean water needs in Tanjungbalai City still faces various challenges, although the potential of raw water sources from the Silau River and drilled wells is quite large. The current clean water distribution system is not optimal in meeting the needs of the community, with a high level of water leakage and inadequate infrastructure. This study aims to analyze the potential of available raw water sources, factors that affect water quality and quantity, and the effectiveness of the clean water distribution system in Tanjungbalai City. The results of the study indicate that high water leakage and old infrastructure conditions are the main problems in clean water distribution. Therefore, the suggested solutions include infrastructure improvements, the application of advanced technology in water treatment and distribution, and diversification of raw water sources to ensure the availability of sustainable clean water for the community. This study is expected to contribute to the management of water resources in Tanjungbalai City.